Biobenefication of Sishen Hematite Iron Ore, using bacterial cultures to remove potassium (Muscovite) and phosphorous (Apatite) - Cloete, T.E. (Thomas Eugene), 1958- (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2011.